Representation of International Criticism of the Middle East Conflict in Arab Cartoons on Instagram - Asror, M. Khozinatul; Muhajjalin, Ahmad Ghuril; Yasykur, Aminuddin; Chotimah, Dien Nur (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
The international community's contribution to the conflict in the Middle East did not provide a solution but rather exacerbated the conflict. This gave birth to various criticisms from various parties, both in the form of oral, written, and image. Using a qualitative descriptive method, this research analyzes five caricatures by @rahma_toons and @hajjaj_cartoons. The theory used in this research is Charles Sanders Peirce's perspective semiotic theory. This research aims to analyze the various elements of icons, indexes, and symbols in the five caricatures uploaded by @rahma_toons and @hajjaj_cartoons. In addition, this study also aims to explain the various icons, indexes, and symbols as a representation of criticism of the conflict that occurred in the Middle East. The results show that the 5 caricatures represent various criticisms. The first criticism is aimed at the UN and Arab countries that only provide symbolic support. The second criticism is aimed at the United States' partiality towards Israel and further aggravating the conflict. The third criticism is aimed at Israel's attack on UNIFIL which shows a violation of international law.